A comparative study of strong ground motion records from the 30 August 2013 south Tibet earthquake on the rock and soil sites of the Kathmandu valley - Bijukchhen, Subeg Man; Takai, Nobuo; Shigefuji, Michiko; Ichiyanagi, Masayoshi; Sasatani, Tsutomu; Rajaure, Sudhir; Dhital, Megh Raj (Journal of Nepal Geological Society, 2016)
The present site response study is based upon strong ground motion records from 4 seismic stations established by the Hokkaido University in the Kathmandu valley at Kirtipur, Tribhuvan University, Patan, and Thimi: one right above the bedrock and others over the lake sediments. We considered the rock-site station in Kirtipur as a reference site to quantify the amplification at sediment sites by analysing the Mb=4.9 Southern Tibet Earthquake of 30 August 2013. The horizontal maximum velocity of 0.84 cm/s is recorded in Thimi in contrast to 0.23 cm/s in Kirtipur. The highest spectral amplitude at sediment sites matches with results from microtremor study. Significant amplification is seen at 0.3-1 Hz band at sediment sites for whole waveform whereas analysis of the S-wave part indicates amplification in the 1-2 Hz band. Surface waves in the records of sediment sites continue for quite a long time compared to that of the rock-site and records of all sites contain Rayleigh waves. Though the difference in azimuth and epicentral distance of the sites are not significant, it is observed that the initial motion at the Kirtipur site is about 0.25 sec earlier than expected. This implies the difference in the underground body wave velocity structure of the sites. But the lack of accurate underground structure of the valley necessitates further study. For future research we will try to discuss the basin underground structure with strong ground motion data including Mb=4.4 Gorkha Earthquake of 25 November 2014 and Mb=5.0 Solukhumbu Earthquake of 18 December 2014.